The Guidelines for Developing Strategic Leadership of School Administrators Under the Office of Roi Et Primary Educational Service Area 2 - Chaengsanam, Kanitha; Duangchatom, Kritkanok (Interdisciplinary Academic and Research Journal, 2023)
Strategic management involves setting school policies and implementing them so that the educational institutions move in the right direction at the heart of the management, with the administrators having to have wise planning. set a different plan from others, but it is a creative difference to be used as a guideline for educational institutions to operate more efficiently. The objectives of this research were (1) to study the current and desirable state of strategic leadership of school administrators, and 2) to study strategic Leadership Development Guidelines for School Administrators. The sample group consisted of 349 school administrators and teachers, and 9 educational experts, consisting of the director of various work groups, education supervisors, and director of educational institutions. The tools used for data collection were questionnaires and interview forms. The consistency index was 0.60 – 1.00, the reliability was 0.98 Statistics used in data analysis were percentage, mean, and standard deviation and Modified Priority Needs Index (PNlModified). The results showed that 1) the current state of strategic leadership of school administrators was at a high level and the desirable state of strategic leadership of school administrators was at the highest level. When considering each side, it was found that the vision setting was at the highest level, followed by the revolutionary way of thinking, respectively. 2) When considering the prioritized needs index of strategic leadership of educational institute administrators, it was found that the desirable conditions were higher than the current conditions (PNlModified = 0.25)